Socio-Economic Prospects and Major Constraints of Vannamei Shrimp Farming in Kerala - A T, Anna; Dinesh, K (Journal of Extension Education, 2023)
Shrimp farming plays a pivotal role in the socio-economic development of the coastal population of India by way of contributing to foreign exchange earnings and livelihood options. In the current study, the culture technique and stocking density are taken into account for investigating the influence of these factors on the production performance and economic feasibility of vannamei shrimp farming in Kerala. Along with the major constraints faced by the Kerala vannamei farmers also undergoing investigation. In recent years, vannamei shrimp farming has been getting excellent responses from shrimp farmers around Kerala due to the attractive and profitable rewards of shrimp farming. Kodungalloor from Thrissur District is a key area in Vannamei shrimp farming in Kerala, more than 60 shrimp farmers are doing Vannamei shrimp farming very enthusiastically and efficiently. But Kerala State still depends on other States to cater to the processing industry which is a highly labour-intensive sector providing the major avocation to thousands of families. Continuous unfavourable weather conditions and delay in the farm registration process led to non-adoption of vannamei shrimp farming in Kerala. Though the State Government support the vannamei shrimp farmers by notifying shrimp farming as an essential activity, our study showed that additional efforts and supports are required to implement solid plans at the ground level.